(untitled) (Medico Legal Update, 2020)
Alternative, collaborative, complimentary, integrative, natural, unconventional and holistic are the terms that are used to describe that do not conform to mainstream allopathic/western/orthodox health approaches. WHO supports traditional and alternative medicines when these have demonstrated benefits for the patient with minimal risks. In general, the harder a medical problem is to treat, the more treatment strategies exist. Patients and physicians are constantly looking for alternatives to drug therapy. Empirical and scientific evidence exists to support the benefits of acupuncture, manual therapies and several medicinal plants for chronic or mild conditions. For instance, the effectiveness of acupuncture, a popular treatment for relieving pain, has been demonstrated both through numerous clinical trials and laboratory experiments. As a result, 90% of pain clinics in the United Kingdom and 70% in Germany include acupuncture as a form of treatment. Acupressure is an easier form of Acupuncture wherein this technique of applying gentle pressure to various ‘pressure points’ on the body is used to cure various Diseases including relief of Pain. The aim of this paper is to give a introduction to acupuncture/acupressure to the general dental practitioner and to understand its history, background, current trends, the relevance and the possibilities of its practice in dentistry.